ANALYSIS OF PHYSICAL AND HEALTH EDUCATION TEACHERS’ PERFORMANCE TOWARD SCHOOL HEALTH UNIT PROGRAM IMPLEMENTATION IN PUBLIC ELEMENTARY SCHOOL IN SUKARAMI DISTRICT PALEMBANG - Reza Resah Pratama (Sriwijaya University Learning and Education International Conference, 2018)
Based on the survey done by the researcher in one of the public elementary schoold in Sukarami district, physical and health education performance and involvement toward school health unit implementation is still unclear, despite the fact that according to the theories and practices, physical and health teachers are those who are directly involved in health field. This research had a purpose to analyze how much is the performance of the physical and health teachers toward the implementation of school health unit program in the public elementary schools in Sukarami District of Palembang. This research was a descriptive research done by doing survey. The population of this research was the physical and health education teachers in public elementary schools in Sukarami district in Palembang, totaling 20 teachers. The instrument used in this research was questionnaire, which will be analyzed by using quantitative descriptive data analysis that uses percentage. The result showed that the performance of physical and health education teachers toward the implementation of school health unit program in public elementary schools in Sukarami district, Palembang, are 40% toward good category, 5% toward very good, 30% toward medium, 10% toward lacking, and 15% toward very lacking. It can be concluded that with a good teacher performance, healthy school environment can be realized, school health unit service performs well, and good physical and health education is maintained well.